THE PRINCIPLE OF NATURAL JUSTICE AND HUMAN’S RIGHT PROTECTION FOR CITIZENS IN ERADICATION OF CORRUPTION IN INDONESIA - Indriyana Dwi Mustikarini (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
There are 550 corruption cases in Indonesia until 25th of February 2016. This number is increasing by the years. This research is meant to find the principal of natural justice and humans’ right protection in corruption eradication. This study is a legal study with statute and conceptual approach. The application of the Act no 31, 1999 related to Humans’ Right and The Act No 28, 1999 related to a clean and corruption, collusion and nepotism free of State Implementation. The collocation of the Act No 31/1999 were influenced by the reformation spirits with respect toward humans right (HAM) whether it is related to deviated action done by bureaucracy apparatus in the form of corruption, has caused the lower society to suffer in this country. This State Implementation action has caused the violation of Human’s Right in economy, social as well as culture as stated in the Act no 31, 1999 and 1945 Constitution. The Act no 28, 1999 related to a clean and corruption, collusion and nepotism free State Implementation stated that the implementation of the principle of natural justice are law assurance, orderly state implementation, public interest, openness, proposisionalism, professionalism, and accountability foundation will be one way to give protection of justice for the citizens toward the state implementation action. The implementation of a principal of natural justice and the maintenance of Human’s right is also a way to eradicate corruption crime in Indonesia. This paper recommends firstly to the government to be consistent to implement the principal of natural justice based on the Act no 28, 1999 related to a clean and corruption, collusion, and nepotism-free state implementation. Secondly, the maintenance of the Act No 31, 1999 related to Human’s Right as a step to eradicate corruption Keywords: The Principle of Natural Justice, Human’s Right, Corruption